2022
DOI: 10.3390/nu14142939
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Food Environments on Food Security Resilience during the COVID-19 Pandemic: An Examination of Urban and Rural Difference in Kenya

Abstract: Hunger and food insecurity has worsened due to the COVID-19 pandemic. The types of food environments (e.g., natural/built) that people can access may improve household resilience to food-system shocks. This paper examines (1) urban and rural differences in the perceived influence of the COVID-19 pandemic on agricultural, livelihoods, food environment attributes, diets; and (2) whether access to different food environments was associated with food security. A two-part telephonic survey (COVID-19 Surveillance Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, by including patients on ART for at least 1 year before DTG switch (median ART duration 6.25 years), the impact on our analysis should be minimal. Finally, the COVID-19 pandemic may have worsened food insecurity, [36][37][38] further attenuating observed weight gain, although this would not invalidate our overall conclusions of low amounts of weight gain in the context of a high degree of food insecurity.…”
Section: Discussionmentioning
confidence: 72%
“…However, by including patients on ART for at least 1 year before DTG switch (median ART duration 6.25 years), the impact on our analysis should be minimal. Finally, the COVID-19 pandemic may have worsened food insecurity, [36][37][38] further attenuating observed weight gain, although this would not invalidate our overall conclusions of low amounts of weight gain in the context of a high degree of food insecurity.…”
Section: Discussionmentioning
confidence: 72%
“…However, in another study, Onyango et al [ 24 ] also focused on the length of stay in the city, rural-urban links, and food transfers, which did not focus on the dietary diversity of households in Nairobi. Nonetheless, the results reported by Onyango et al [ 22 ] are further supported by Merchant et al [ 23 ], who found that urban households reported lower food security outcomes than rural households because of decreased access to the food production environment resulting from COVID-19 restrictions on movement and lockdowns.…”
Section: Conceptual Approachmentioning
confidence: 79%
“…Ericksen [ 25 ] also identifies other factors, such as access to government and non-government social support services, as food production and consumption determinants. Besides the rural-urban food continuum, employment, education, household income, and food prices also determine food security outcomes [ 23 , 24 ]. These studies highlight the importance of socioeconomic variables in determining food security.…”
Section: Conceptual Approachmentioning
confidence: 99%
See 2 more Smart Citations